Decision Support System uses Multi-Objective Optimization By Ratio Analysis (MOORA) Method in Selection of the Best Herbal Medicine Supplier - Andriyan Buyung Septyanta; Dinul Akhiyar (Universitas Putra Indonesia YPTK Padang, 2024)
Jamu is a traditional medicine made from natural cultural heritage that has been passed down from generation to generation for health. Mbak Sum UKM is a small and medium enterprise that operates in the field of medicines, namely herbal medicine, where this business provides various types of herbal medicine. This herbal medicine business is a business that can promise business opportunities. Because there is so much interest in this natural herbal concoction, it makes it difficult for companies to meet product availability. And this makes SMEs need many suppliers to meet product availability for Mbak Sum's SMEs. Therefore, a system is needed to help Mbak Sum's SMEs overcome the problems they face. The system that will help Mbak Sum's UKM is a decision support system in selecting quality suppliers which will later help in fulfilling herbal herbal products in Mbak Sum's UKM as well as in making reports of incoming products from suppliers to Mbak Sum's UKM. The system built to support supplier selection decisions uses the multi-objective optimization by ratio analysis (MOORA) method. The MOORA (Multi-Objective Optimization On The Basis Of Ratio Analysis) method is a multi-objective optimization technique that can be successfully applied to solve various types of complex decision-making problems in decision making. The results obtained were that the first rank was Alternative 3 with a value of 0.284 and the sixth rank was Alternative 6 with a value of 0.164. The calculation process can be concluded that A3 is the best alternative